The role of television talk shows in shaping the political awareness of the students of Diyala University - العبيدي دحام علي حسين (ALBAHITH ALALAMI, 2015)
The study aimed to exposure young university students and students talk programs offered by satellite TV exposure, as it represents these programs great importance Information Public Knowledge in general And the youth in private Including Posed From Opinions And ideas About Different Issues Raised Which Charges Opinion, And that Through Application Study Survey To Sample From Students of Diyala University, the Researcher display Public Accrediting Theory To Information Which Provided Means Media To achieve Objectives And satisfy Needs And hypotheses . The Problem Search was Determined Through Study of students of Diyala University exposure Programs Talk And measured Role These Programs As One Means To express their Views In Formation Knowledge? Against Political Issues, That What Provided These Programs Different Opinions about Different Political Issues Which consider Public Interest for Iraqi people. The Determination Type ( Gender ) Variable Independent And its relationship With Type Programs, The Achieved By the Exposure Programs Talk And adopted The study To Use of Method Survey, The Adopted Researcher Style Sample Random, The total Size Sampler (180) Single Distributed To Students Male and female Evenly. To address Data Statistical Account the data Statistics and percentages and the use of Ca 2 square test to measure the relationship with the variables, and Pearson correlation coefficient to conduct stability. The study was summarized to some results: • Not Presence Differences Function Statistically between Variable Gender And the extent of Show Programs Talk Which Exposure TV Channels. • There are significant differences between the sex variable and the reasons for not watch talk shows offered by TV satellite. • Not Presence Differences Function Statistically Between Variable Gender the reasons Show Talk Programs. • Not Presence Differences Function Statistically between Variable Gender the issues that the public are keen to follow the programs talk shows. 5. Not Presence Differences Function Statistically between Variable Gender And the extent of public confidence in the talk show programs.